Tuneable Acidity in Fluorinated Al-SBA-15 Materials for the Esterification of Valeric Acid to Alkyl Valerates - Blanco-Sánchez, Miguel; Pfab, Evan; Lázaro, Noelia; Balu, Alina M.; Luque, Rafael; Pineda, Antonio (Frontiers in Chemistry, 2020)
The acidity of Al-SBA-15 materials functionalized by ball milling with several niobium loadings (0.25–1 wt.%) as well as with several fluorine loadings (by wet impregnation using NH4F as a precursor) was characterized and materials investigated in the esterification of valeric acid to alkyl valerates. The parent Al-SBA-15 support as well as the modified materials loaded with Nb and/or F have been catalysts synthesized characterized by X-ray diffraction (XRD), N2 physisorption measurements, and diffuse reflection infrared spectroscopy (DRIFT) among others. A special interest was paid on the acidity of the materials that was investigated by temperature-programmed desorption of pyridine. Interestingly, the characterisation results for the materials containing fluorine showed up an increase in the acidity strength despite of a reduction in the number of acid sites. The catalytic performance of the as-prepared catalysts was investigated in the microwave-assisted esterification reaction of valeric acid to valerate esters. Thus, while the materials modified with niobium exhibited a lower catalytic activity as compared with the catalytic support (Al-SBA-15), the materials loaded with fluorine either onto Al SBA-15 or on Nb1%/Al-SBA-15 materials presented enhanced conversion values of valeric acid. Therefore, it can be said that the new acid sites with enhanced strength formed by the incorporation of fluorine boost the esterification of valeric acid with alcohols to form the respective valerate ester.